Anglo Libyan relations and the British military facilities 1964-1970 - Straw, Sean William (2011)
This study explores the role of the Anglo-Libyan relationship and the British military facilities in the Labour Government’s foreign and defence policy from 1964 to 1970. This relationship, built upon a “shared tradition” of strategic self interest, was given form in the 1953 treaty which permitted British deployments. The military presence enabled the British to maintain their wider strategic interests East of Suez as well as provide security for the Idris regime in Tripoli. As the Labour Government made cuts in Britain’s defence policy, Libya lost its strategic value but grew in importance for the trade opportunities it offered. In line with defence cuts and a Libyan withdrawal request in 1967, the facilities were scaled back. The remaining presence enabled the British to exploit the growing Libyan economy and maintain influence and defence interests in the country. Tripoli grew increasingly unnerved by the political and territorial ambitions of its Arab Nationalist neighbours, Egypt and Algeria, whilst London regarded Libya as vulnerable to economic and political penetration from the Soviet Union, placing the relationship within the context of the Cold War and Western security. As a consequence the Labour Government encouraged the Libyans to take greater responsibility for their defence, exporting arms to Tripoli and welcoming attempts by Prime Minister Al-Bakkoush to develop the country using oil revenue. After the 1969 Libyan revolution the Labour Government, concerned by the strategic implications of an Arab Nationalist regime in Tripoli, sought to secure Britain’s position and steer the regime away from participating in the Arab-Israeli conflict. However, Tripoli was no longer politically inclined towards the West and London’s attempt to forge a relationship, using existing arms contracts, was complicated by the contentious issue of the sale of Chieftain tanks negotiated with the previous regime. Negotiations floundered and British interests, including a residual presence were lost. Not until thirty years later did the relationship regain any of its former geniality as a strategic “shared tradition” re-emerged to bring the two nations together once more.